Decolonial Perspectives in English Language Classroom: A Thematic Review - Gurung, Bhabishor (Nepalese Linguistics, 2025)
The purpose of this study is to decolonize the hegemonic legacy of the English language in the Nepali education system by  adopting a thematic analysis as the research method. The academic databases like ERIC, Google Scholar, and JSTOR were employed to gather the data for the study. Three different themes were seemingly developed from study of relevant resources which included teachers’ initiation in decolonial practices to enhance language learning, policy-level shifts in decolonial practices, and paradigms in promoting decolonial practices in English language education. This paper will contribute to the Nepalese English academia, fostering their languages and cultural identities in a compatible way through the use of English without the strict resistance of it.